Using video lectures to make teaching more interactive - Ronchetti, Marco (International Journal of Emerging Technologies in Learning (iJET), 2010)
Having worked for a long time with video-lectures, we devised a new teaching model that makes use of the recorded videos to free the teacher from part of his work and allowing him to concentrate his efforts on a more effective and involving teaching strategy.